2017
DOI: 10.1016/j.jaut.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding the pathogenesis of scleroderma through genomics and epigenomics

Abstract: With unknown etiology, scleroderma (SSc) is a multifaceted disease that comprises of immune activation, vascular complications, and excessive fibrosis in internal organs. Genetic studies, including candidate gene association studies, genome-wide association studies, and whole-exome sequencing have supported the notion that while modest, SSc patients are genetically predisposed to this disease. The strongest genetic association for SSc lies within the MHC region, with loci in HLA-DRB1, HLA-DQB1, HLA-DPB1, and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 192 publications
(233 reference statements)
3
67
0
Order By: Relevance
“…WNT5A, and Wnt signaling more generally, have been implicated in many processes known to be involved in SSc pathogenesis (Tsou and Sawalha 2017;Wei et al 2011;Katsumoto et al 2011;Lafyatis 2012), such as angiogenesis (Huang et al 2005), keratinocyte differentiation and inflammation signaling , and fibroblast proliferation (Vuga et al 2009). WNT5A has also been linked to cellular transdifferentiation, a family of processes by which differentiated cell types dedifferentiate and redifferentiate into another cell type.…”
Section: Discussionmentioning
confidence: 99%
“…WNT5A, and Wnt signaling more generally, have been implicated in many processes known to be involved in SSc pathogenesis (Tsou and Sawalha 2017;Wei et al 2011;Katsumoto et al 2011;Lafyatis 2012), such as angiogenesis (Huang et al 2005), keratinocyte differentiation and inflammation signaling , and fibroblast proliferation (Vuga et al 2009). WNT5A has also been linked to cellular transdifferentiation, a family of processes by which differentiated cell types dedifferentiate and redifferentiate into another cell type.…”
Section: Discussionmentioning
confidence: 99%
“…As in many other autoimmune diseases , genetic predisposing factors have been shown to be associated with disease progression in PBC. For example, epidemiological data indicated an increased prevalence of patients with PBC among first‐degree relatives and siblings of an index patient, in what is known as familial clustering of PBC .…”
Section: Contribution Of Environmental Triggers To Pbcmentioning
confidence: 98%
“…This indicates an 'epi' genetic component to the etiopathogenesis of these diseases. Studies in SLE, RA, Sjogren's syndrome, scleroderma and recently vasculitis have suggested and confirmed this fact [3][4][5][6]. However, we are still in need of studies on Ax SpA where the strong association with a gene (HLA B27) was revealed almost 3 decades ago [7] and yet, the exact association between the HLAB27 gene and Ax SpA still remains unexplained.…”
Section: Introductionmentioning
confidence: 98%